Rapid changes in public perception toward a conservation initiative. Issue 4 (10th February 2022) - Niemiec, Rebecca; Berl, Richard E. W.; Gonzalez, Mireille; Teel, Tara; Salerno, Jonathan; Breck, Stewart; Camara, Cassiopeia; Collins, Matthew; Schultz, Courtney; Hoag, Dana; Crooks, Kevin
Abstract: Rapid, widespread changes in public perceptions and behaviors have the potential to influence conservation outcomes. However, few studies have documented whether and how such shifts occur throughout the span of a conservation initiative. We examined the 2020 ballot initiative to reintroduce wolves into Colorado, which passed with less support than prior surveys had estimated. We conducted a postelection survey of Colorado residents using the same methods as our preelection survey to compare responses between surveys and to official election results. Reported voting in favor of wolf reintroduction in the postelection survey decreased in comparison to voting intentions shared in the preelection survey, but not enough to reflect the actual vote. While bias from survey methods and/or sampling contributed to differences, we also found evidence that public perception changed. Specifically, beliefs about the potential for negative impacts of wolves increased, while beliefs about the potential for positive impacts of wolves decreased. Our findings highlight the need to conduct longitudinal monitoring of public perception given perceptions may be highly fluid as different entities attempt to sway voters. In addition, to better understand evolving perceptions, survey methods and sampling need to be improved. Abstract : We find evidence of rapid, widespread public perspective change in response to a conservation initiative: the ballot initiative to reintroduce wolves to Colorado. We also find evidence that online panel surveys can overestimate public support for conservation causes, particularly in rural areas.